Computational fluid-structure interaction methods and applications - Bazilevs, Yuri.; Takizawa, Kenji; Tezduyar, T. E. (Tayfun E.) (Hoboken : John Wiley & Sons Inc., 2013)
"Computational Fluid-Structure Interaction is a complete, self-contained reference that takes the reader from the fundamentals of computational fluid and solid mechanics all the way to the state-of-the-art in CFSI research"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Fluid-structure interaction -- Data processing; Fluid-structure interaction -- Mathematical models; Electronic books